Day-to-Day Dynamics of Commensal Escherichia coli in Zimbabwean Cows Evidence Temporal Fluctuations within a Host-Specific Population Structure - Massot, Méril (Appl Environ Microbiol, 2017)
To get insights into the temporal pattern of commensal Escherichia coli populations, we sampled the feces of four healthy cows from the same herd in the Hwange District of Zimbabwe daily over 25 days. The cows had not received antibiotic treatment during the previous 3 months. We performed viable E. coli counts and characterized the 326 isolates originating from the 98 stool samples at a clonal level, screened them for stx and eae genes, and tested them for their antibiotic susceptibilities. We observed that E. coli counts and dominant clones were different among cows, and very few clones were shared. No clone was shared by three or four cows. Clone richness and evenness were not different between cows. Within each host, the variability in the E. coli count was evidenced between days, and no clone was found to be dominant during the entire sampling period, suggesting the existence of clonal interference. Dominant clones tended to persist longer than subdominant ones and were mainly from phylogenetic groups A and B1. Five E. coli clones were found to contain both the stx(1) and stx(2) genes, representing 6.3% of the studied isolates. All cows harbored at least one Shiga toxin-producing E. coli (STEC) strain. Resistance to tetracycline, penicillins, trimethoprim, and sulfonamides was rare and observed in three clones that were shed at low levels in two cows. This study highlights the fact that the commensal E. coli population, including the STEC population, is host specific, is highly dynamic over a short time frame, and rarely carries antibiotic resistance determinants in the absence of antibiotic treatment. IMPORTANCE The literature about the dynamics of commensal Escherichia coli populations is very scarce. Over 25 days, we followed the total E. coli counts daily and characterized the sampled clones in the feces of four cows from the same herd living in the Hwange District of Zimbabwe. This study deals with the day-to-day dynamics of both quantitative and qualitative aspects of E. coli commensal populations, with a focus on both Shiga toxin-producing E. coli and antibiotic-resistant E. coli strains. We show that the structure of these commensal populations was highly specific to the host, even though the cows ate and roamed together, and was highly dynamic between days. Such data are of importance to understand the ecological forces that drive the dynamics of the emergence of E. coli clones of particular interest within the gastrointestinal tract and their transmission between hosts.